MUHAMMAD IQBALâS PHILOSOPHY OF RELIGION AND POLITICS: The Basic Concept of Religious Freedom - Tajuddin, Muhammad Saleh (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
The objective of this writing is to explore Iqbalâs thought about religion and politics as the basic concepts of religious freedom. This writing is done by doing research in library and running qualitative research based on philosophical approach. The study is analyzed through descriptive analysis to get accurate results from the objective of the study. The results of the research are: 1) Iqbalâs thought of religion is based on creed (belief), which reflects on rational thought. Iqbalâs effort on reconstruction of religion gives harmony between religion and politics which leads to the society too. 2) The religious freedom from Iqbalâs thought is based on the political ethics concept. His idea is started with the integration between Western thoughts and the Qurâan. Iqbalâs perspective of ego promotes self freedom, so every person can avoid his self from getting perfect spiritual (insane kamil). 3) Individual that lives in âreality as self consciousâ concerns on the powers, which will create a harmony to society. Â ———-Tujuan penulisan ini adalah untuk mengeksplorasi pemikiran agama dan politik Muhammad Iqbal sebagai landasan pemikirannya tentang kebebasan beragama. Tulisan ini menggunakan metode library research dengan jenis penelitian kualitatif melalui pendekatan filsafat. Hasil temuan tulisan inin adalah: 1)Pemikiran keagamaan Iqbal didasarkan pada iman kemudian direfleksikan dalam bentuk pemikiran rasional. Upaya Iqbal dalam merekonstruksi pemikiran agama adalah memberikan keharmonisan pada agama dan politik dalam mencapai kehidupan sosial yang harmoni. 2) Pemikiran Iqbal tentang politik sebagai dasar kebebasan beragama adalah didasarkan pada konsep etika politik. Dasar pemikirannya diawalidengan konsep diri dengan memadukan pemikiran Barat dengan Alquran. Ego bagi Iqbal adalah kausalitas pribadi yang bebas, sehingga setiap individu mesti mampu mengendalikan dirinya untuk mencapai kesempurnaan spiritual (InsanKamil). 3) Individu sebagai reality as self conscious adalah suatu kesadaran akan kekuatannya, dan kesadaran akan tujuan hidupnya yang besar bergabung dalam masyarakat untuk mewujudkan tatanan kehidupan yang harmonis.